Criminal Law Enforcement for Misuse of Cytotec Drugs that Provides Legal Certainty - Wijaya, Diki; Setiadi, Edi; Mahmud, Ade (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
This research aims to determine criminal law enforcement regarding acts of misuse of Cytotec drugs which provides legal certainty. Legal regulations concerning abortion practices in Indonesia have evolved to address societal changes and ethical considerations in medicine. According to Indonesian law, medical professionals are prohibited from performing abortions, aligning with religious doctrines and ethical standards. The Indonesian Doctor's Oath, based on the Geneva Declaration and enhancing the Hippocratic Oath, underscores the commitment to respect human life from conception onwards. This normative research utilizes secondary data initially, followed by primary data collection, to examine empirical-juridical aspects related to the enforcement of laws concerning Cytotec misuse for abortions, considering legal certainty principles. This research found that the previous Health Law until now is still consistent in prohibiting abortion except in cases that have been determined by law.